(untitled) (Eurasian Research Bulletin, 2025)
This article analyzes the foreign experience of implementing the tax administration of large taxpayers, as a result of this analysis, issues of improving the tax legislation of the Republic of Uzbekistan, a proposal for further improvement of the tax administration of large taxpayers and recommendations are developed